Vulnerability of ecosystems with Guadua angustifolia in Ecuador in light of climate changes - Mario José Añazco Romero (Pesquisa Agropecuária Tropical, 2019)
Guadua angustifolia bamboo is historically used by an important percentage of the rural and peri-urban population of Ecuador, especially in the construction of bridges, when events like El Niño and its consequential flooding occur. This study aimed to determine, in light of some climate change scenarios, the vulnerability rate of ecosystems where the G. angustifolia bamboo species occurs, in the coastal region of continental Ecuador. The analysis methodology, with focus on the sampled units, was based on vulnerability assessment tools for climate adaptation recommended by the Intergovernmental Panel on Climate Change. Temperature presented the highest correlation coefficient with the vulnerability rate of the ecosystems, followed by the increase in the sea level, winds and landslides. It was concluded that as the exposure and sensitivity variables increase, the adaptive capacity of ecosystems with occurence of this species decreases, and isolated plants and monoculture plantations are the most vulnerable to climate changes.